Pregnancy Health Education for Pregnant Adolescents: Evaluation of the Effectiveness of Counseling Programs in Schools - Andi Muhammad Multazam; Olyvia Rosalia; Firayani (Oshada, 2025)
Adolescent pregnancy remains a global health concern, necessitating effective educational interventions to improve maternal and child health outcomes. This study aims to evaluate the effectiveness of pregnancy health counseling programs for adolescents within school settings through a Systematic Literature Review (SLR) guided by the PRISMA framework. A total of 239 articles were retrieved from databases such as Google Scholar, Scopus, SINTA, GARUDA, Crossref, and ICI. After a rigorous selection process based on predefined inclusion and exclusion criteria, only 25 articles were deemed eligible for in-depth analysis. The findings indicate that school-based pregnancy counseling programs significantly enhance adolescents’ knowledge, attitudes, and behaviors regarding maternal health. Various counseling methods, including face-to-face sessions, group discussions, and digital interventions, contribute to program effectiveness. However, challenges such as limited resources, social stigma, and accessibility barriers hinder program implementation. This study underscores the importance of integrating pregnancy health education into school curricula, leveraging technology for broader reach, and fostering collaboration between schools, healthcare professionals, and families. Future research should explore long-term impacts and the role of cultural factors in shaping program outcomes.